Stepwise Optimization of I-section Flexible Elements Under a Fuzzy Approach to Taking into Account Corrosion and Protective Properties of Anticorrosive Coating - Fridman, M.M. (Проблеми машинобудування, 2018)
This paper is a continuation of research in the field of optimal design of structures under a combined approach to the measurement of corrosion and anticorrosion protective properties of coatings. Ця робота є продовженням дослідження в області оптимального проектування конструкцій при комбінованому підході до обліку корозії і антикорозійних захисних властивостей покриттів. Данная работа является продолжением исследования в области оптимального проектирования конструкций при комбинированном подходе к учету коррозии и антикоррозионных защитных свойств покрытий.